2017
DOI: 10.21608/eajbsg.2017.16329
|View full text |Cite
|
Sign up to set email alerts
|

Submerged Fermentation of Jatropha curcas Seedcake in Production of Itaconic Acid by Aspergillus niger and Aspergillus terreus

Abstract: Microbiology journal is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the research across the whole spectrum of the subject. These including bacteriology, virology, mycology and parasitology. In addition, the journal promotes research on the impact of living organisms on their environment with emphasis on subjects such a resource, depletion, pollution, biodiversity, ecosystem…..etc www.eajbs.eg.net Provided fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The high percentages of carbohydrates and protein (carbon and nitrogen sources, respectively) observed in sweet potato peels in this study demonstrated its suitability as good substrate candidate for microorganisms to thrive and for the production of organic acids. This corroborates the findings of Omojasola and Adeniran (2014), where sweet potato peel recorded high carbohydrate content as a great hot spot for microbial activities. High carbohydrate content that is easily metabolized is essentially required as a substrate for fungi in the fermentation process for optimum production of itaconic acids (organic acids) (Max et al, 2010;Ajiboye et al 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The high percentages of carbohydrates and protein (carbon and nitrogen sources, respectively) observed in sweet potato peels in this study demonstrated its suitability as good substrate candidate for microorganisms to thrive and for the production of organic acids. This corroborates the findings of Omojasola and Adeniran (2014), where sweet potato peel recorded high carbohydrate content as a great hot spot for microbial activities. High carbohydrate content that is easily metabolized is essentially required as a substrate for fungi in the fermentation process for optimum production of itaconic acids (organic acids) (Max et al, 2010;Ajiboye et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Fungi (A. niger and A. flavus) via amylolitic action convert polysaccharides into sugars (reducing and non-reducing sugars) during fermentation, accounting for the rise in reducing sugar content up until day 5. This process may also consequently produce an elevated level of itaconic acid (Petruccioli et al, 1999;Omojasola and Adeniran, 2014). The findings of Ahmed El-Imam et al (2013) and Ajiboye et al (2018), who worked on Jatropha oilseed cake and Date pulp (Phoenix dactylifera L.), respectively, are similar in that they found itaconic acid concentration increased with an increase in substrate concentration with a maximum yield at 40 g. The noticeable decline might be explained by the fungi consuming all of the necessary nutrients.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Crude protein levels in raw JSC were 27.35%, similar to the levels reported in the literature, which vary from 28.87% to 37.82% [56]. Some studies indicate an increase in concentrations of crude protein on JSC around 8%, when treated with Absidia spinosa and Mucor rouxii [57], or a reduction when treated with Trichoderma longibrachiatum, Trichoderma harzianum, and A. niger [58].…”
Section: Bromatological Analysis Of the Fermented Ssf-jsc And Ssf-cscsupporting
confidence: 76%
“…The bioconversion of SPP to organic acids has been studied by some researchers, and most commonly used strain is A. niger. Some researchers used A. niger to ferment SPP for the production of itaconic acid (Omojasola & Adeniran, 2014). They found that the fermentation conditions of pH 4.0, 5% inoculum concentration, 10% SPP concentration, 25 • C, and 5 days resulted in the highest yield of 112.67 mg/mL.…”
Section: The Production Of Organic Acidmentioning
confidence: 99%